A Power Control Scheme For Doubly-fed Induction Generator - Alfeu J. Sguarezi Filho; M. E. Oliveira Filho; Ernesto Ruppert (Eletrônica de Potência)
This paper proposes a power control scheme for doubly-fed induction generator for variable speed wind power generation. This scheme uses stator flux decoupling and deadbeat control loops. The algorithm of the deadbeat calculates the voltage vector to be supplied to the rotor in order to guarantee that the active and reactive power reach their desired reference values. Because the generator leakage inductance and resistance information were required for this control method, the influence of the estimation errors for these parameters was also investigated. Simulations results are carried out for validation of the digital controller operation.